DIAGNOSTIC OF THE LEVEL OF SATISFACTION OF PHYSICAL EDUCATION PROFESSIONALS REFERENT TO THE MARKET BASED ON THE INFRA-STRUCTURE PERSPECTIVES, REMUNERATION AND SOCIAL ACCEPTANCE (Fiep Bulletin - online, 2013)
We Know that the market has become more selective , on the other hand, it is more receptive to well prepared professionals, this study comes to assist the Professionals of Physical Education to be integrated in the reality found in the work market. A parallel between work market and the Professional of Physical Education in the social, structural and of remuneration context was created in order to discover the level of satisfaction of the same ones in the main areas of performance.
Keywords: working market; Satisfaction; Physical education